2021
DOI: 10.1002/adfm.202103655
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Actuated Active Deep Tumor Penetration of Deformable Large Nanocarriers for Enhanced Cancer Therapy

Abstract: The intrinsic pathological microenvironment of tumor tissue enforces barriers to the passive diffusion of nanomedicine, which results in inefficient tumor penetration of drugs and unsatisfactory therapeutic efficacy. Various strategies have been developed to improve the tumor penetration of nanomedicine, but they mostly overcome the barriers separately at different steps in a passive diffusion process. Here, the development of a large polymeric nanocarrier, DA T-PPE D&F (≈180 nm), is reported, which comprises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 53 publications
(73 reference statements)
0
29
0
Order By: Relevance
“…Among the various strategies for nanocarriers to cross the BBB, utilizing specific receptors that are expressed at the BBB for active targeting is the most commonly preferred method due to its noninvasive and feasible characteristics. [11][12][13] In recent years, pioneering studies have confirmed that the lowdensity lipoprotein receptor-related protein-1 (LRP-1) is overexpressed not only at the BBB but also at the cytoplasm and surface of the GBM cells. 14 Due to its dual targeting mechanism and higher efficiency than lactoferrin, transferrin and avidin, angiopep-2 (Ang, a targeted peptide for LRP-1) has emerged as a more ideal candidate for nanocarrier modification to facilitate their BBB penetration and subsequent internalization by brain parenchymal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various strategies for nanocarriers to cross the BBB, utilizing specific receptors that are expressed at the BBB for active targeting is the most commonly preferred method due to its noninvasive and feasible characteristics. [11][12][13] In recent years, pioneering studies have confirmed that the lowdensity lipoprotein receptor-related protein-1 (LRP-1) is overexpressed not only at the BBB but also at the cytoplasm and surface of the GBM cells. 14 Due to its dual targeting mechanism and higher efficiency than lactoferrin, transferrin and avidin, angiopep-2 (Ang, a targeted peptide for LRP-1) has emerged as a more ideal candidate for nanocarrier modification to facilitate their BBB penetration and subsequent internalization by brain parenchymal cells.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in good agreement with previous findings, demonstrating that tumor pH substantially enhances the internalized DA TAT-NP VT content by recovering its TAT ligand function. 56,57…”
Section: Resultsmentioning
confidence: 99%
“…These results are in good agreement with previous findings, demonstrating that tumor pH substantially enhances the internalized DA TAT-NP VT content by recovering its TAT ligand function. 56,57 3.3 Cell killing of DA TAT-NP VT in vitro According to our design, the increased intracellular VP content could improve the efficiency of X-PDT treatment under external X-ray exposure. Subsequently, the hypoxic condition induced by radiotherapy and PDT would activate TPZ to release cytotoxic oxidizing radicals for efficient chemotherapy.…”
Section: Preparation and Characterization Of Da Tat-np Vtmentioning
confidence: 96%
“…1i), confirming that USIO was typically ferromagnetic, consistent with the previous report. 33 However, unlike the Scheme 1 Schematic illustration of the preparation of iAIO@NSe-Pt and the synergistic actions of anti-angiogenesis, chemo-, and chemodynamic therapy induced by iAIO@NSe-Pt.…”
Section: Physico-chemical Property Of Iaio@nse-ptmentioning
confidence: 99%